The Cleaning Performance and Sanitary Condition of Acrylic Fiber Dish Cleaner - IYADOMI, Minako; ENOMOTO, Masao; KAI, Kyoko (Journal of Home Economics of Japan, 2001)
To verify the cleaning performance and sanitary condition of acrylic fiber dish cleaner, which is used without detergent, we compared its cleaning performance with that of sponge dish cleaner, which is used with detergent. The following results were obtained. (1) It was proved that the cleaning power of acrylic fiber dish cleaner is equivalent, under certain conditions, to that of sponge dish cleaner used with kitchen soap or synthetic detergent. (2) In the case of cleaning a polypropylene dish having residue of hot hamburger steak, the cleaning power of the acrylic fiber dish cleaner was low when the temperature of the water was low. However, as the water temperature increased, so did the cleaning power, to the point of being equivalent to that of the sponge dish cleaner used with kitchen soap. (3) The sanitary condition of acrylic fiber dish cleaner after being used can sufficiently be maintained using a simple method such as washing with kitchen soap, as in the case of cleaning a dish having residue of hot hamburger steak. However, in the case of cleaning a dish having residue of uncooked food such as raw fish, chlorine disinfection is necessary in addition to washing with kitchen soap.